Pengaruh Pengendalian Manajemen Piutang Terhadap Likuiditas dan Profitabilitas PT Bank Syariah Indonesia yang Terdaftar di Bursa Efek Indonesia - Safwa Al Zafitri; Syahriyah Semaun; Damirah Damirah; Muzdalifah Muhammadun; Andi Ayu Frihatni (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study examines the effect of accounts receivable management measured through indicators such as Days Sales Outstanding (DSO), receivable turnover, and collection period on the financial performance of companies. The research was conducted using a quantitative approach with secondary financial data collected from company reports. Statistical analyses were performed to evaluate whether efficient receivable management contributes to improvements in liquidity, profitability, and overall financial stability. The results show that shorter DSO and higher receivable turnover are strongly associated with enhanced financial performance, as reflected in indicators such as Return on Assets (ROA), Return on Equity (ROE), and the Loan to Deposit Ratio (LDR). These findings indicate that effective receivable management plays a crucial role in strengthening a firm’s financial position and operational efficiency. This study contributes to the growing body of literature highlighting receivables as a strategic component in corporate financial decision-making and provides useful insights for managers in optimizing credit policies to support sustainable financial performance.